Effecting a regional plan for progress. - Charles, Eugenia (1991)
Discusses measures which must be taken if the goals of economic cooperation are to be achieved. These include fiscal and monetary policies, dismantling all non-tariff barriers to trade, coordination in exchange rate regime for all the currencies, and the liberalisation of the movement of capital and investment.